TEKNIK MEMBACA BUKU DENGAN MEMBUKA-BUKA BUKU - Iswara, Prana Dwija (Universitas Pendidikan Indonesia, 2014)
Openning book is one of human daily activities when they read books. When someone openning book, she or he has not done something that does not have any purpose. There are many benefits in opennig book activities, one of them is retrieving comprehension as much as possible. Openning book means repeatedly openning the pages, reading important portion of the page and skipping less important portion of the page. Openning books activity can be being done in a relatively short time (e.g. five minutes or half an hour) and will have been completed once at a time. Openning book reading technique can be used even by the students in elementary school. Therefore, openning book reading technique is claimed to be the one of important reading technique for reading study. Keywords: repeatedly openning the page, openning book, reading, elementary school.